Perancangan Keyway Slotting Machine Untuk Lebar Alur Pasak 4mm - 10mm dan Kedalaman 1,2mm – 2,4mm Menggunakan Metode TRIZ - Sitompul, El Nathan; Heri Widiantoro (Jurnal Teknik Mesin Indonesia, 2024)
Key is a critical component in mechanical applications of transmission systems to transfer power and torque from the shaft to its hub. The precise creation of the internal keyway is crucial to ensure a strong and reliable connection. The lack of suitable equipment for making internal keyways poses a barrier in practical applications. By utilizing a combination of TRIZ approaches and the Pahl & Beitz design methodology, the design process generates innovative concepts to be integrated into the selected design concept. The final design specifications include a maximum clamping capacity of ∅100mm, a minimum inner hub diameter of ∅10mm, groove width ranging from 4mm to 10mm, and groove depth from 1.2mm to 2.4mm in accordance with DIN 6885 standards. Additionally, the implementation of speed control and automatic emergency systems enhances operational safety in abnormal conditions.